Effect of phosphoric acid as slurry additive on Li4Ti5O12 lithium-ion anodes. (10th October 2022) - Xu, Yun; Mullaliu, Angelo; Lin, Shawn D.; Ma, Yanjiao; Asenbauer, Jakob; Zarrabeitia, Maider; Passerini, Stefano; Bresser, Dominic
Abstract: The aqueous processing of lithium-containing electrode materials is challenged by the reactivity of such materials towards water, resulting in lithium leaching, slurry pH increase, and consequent corrosion of the aluminum current collector. The addition of (mild) acids to the aqueous electrode slurry has been reported as a viable method to suppress the corrosion issue. Herein, we present a comprehensive investigation of the addition of phosphoric acid (PA) to an aqueous electrode slurry containing Li4 Ti5 O12 as the active material. Following an initial evaluation of the slurry pH evolution as a function of the PA content, a comparative investigation of the PA-free electrodes and the "corrosion-free" electrodes was performed. The latter clearly outperform the PA-free electrodes in terms of their electrochemical performance. Interestingly, this is not only resulting from the buffered pH, but the phosphate anion also plays a decisive role.